Trypanotolerance in cattle and prospects for the control of trypanosomiasis by selective breeding - Murray, M.; Trail, J.C.M.; D'Ieteren, G.D.M. (1990)
Discusses trypanotolerance in cattle and prospects for the control of trypanosomiasis by selective breeding in Africa. Looks into methods available for control including tsetse control, drugs & vaccination and discusses constraints that limit the control. Also discusses prospects for future control. Includes data on mean parasitaemia score and packed red cell volume (PCV) of N'Dama and Boran cattle infected with Trypanosoma Congolense.